Pengaruh Ekonomi Hijau dan Bisnis Bertanggung Jawab Sosial Terhadap Risiko Kebangkrutan dan Risiko Sistematis dengan Komite Audit sebagai Intervening - Mamta Sartika; Nera Marinda Machdar (UNIVERSITAS KALBIS, 2022)
This study discusses the influence of green economy and social responsible business on bankruptcy risk and risk of systematic with the audit committee as intervening. Study aims to examine the effect of a green economy and social responsible business on bankruptcy risk; to examine the effect of a green economy and social responsible business on risk of systematic; and to examine the influence of the audit committee indirectly on the relationship of green economy and social responsible business. The sample selection method uses purposive sampling in companies listed on the Indonesia Stock Exchange in 2013-2018. There are 97 companies that meet the criteria as a research sample. The method of analysis uses multiple linear analysis using the program Eviews 10. The test results show that the green economy has a positive effect on the risk of bankruptcy, while social responsible business has a negative effect on the risk of bankruptcy. Green economy and social responsible business negatively affect risk of systematic. The audit committee has no effect on bankruptcy risk and risk of systematic and cannot indirectly affect the green economy and social responsible business.